Edukasi Penerapan Perawatan Mandiri di Rumah pada Pasien Terkonfirmasi Covid-19 Tanpa Gejala di Puskesmas Batua Makassar - Elly Lilianty Sjattar; Abdul Majid; Rosyidah Arafah; Yuliana Syam; Indra Gaffar (PT.Mantaya Idea Batara, 2021)
Coronavirus Disease-2019 (Covid-19) is an infectious disease caused by a new type of coronavirus, namely SARSCoV-2. On March 11, 2020 WHO declared Covid-19 a pandemic. Since December 2019, the number of confirmed cases of COVID-19 has continued to increase. In Indonesia, on January 17, 2021, there were 917,015 cases with a death toll of 2.8% of the total confirmed cases. South Sulawesi Province as much as 4.5% of the total confirmedcases in Indonesia or 41,697 people and Makassar City is the location with the most positive confirmed cases in South Sulawesi, namely 20,674 people. By looking at this situation, the government has instructed the public to selfisolate if confirmed positive for Covid-19 without symptoms. Therefore, the public needs to understand how toperform self-care while self-isolating. Through this community service, with the online method using the media zoommeeting, health education, video screenings, discussions and questions and answers are carried out. The results of this community service show that there are many participants who ask questions either directly or through chatmedia, and the evaluation results from the questionnaires given show a good understanding. Health educationactivities for Covid-19 patients who are doing self-care at home are very important, to prevent the risk of transmission to family members who live at home, Covid-19 patients are calmer in the treatment process, families can be involved in the treatment process, and can recover optimal.Keywords : Self care, Covid-19, Education, Community Service.